Explanation of the problems of my father's hair Tammam Abu Hamid Ahmed bin Muhammad Al-Bashti Al-Kharzanji The deceased in 348 AH (Journal of the College of Basic Education, 2022)
Praise be to God, Lord of the worlds, and prayers and peace be upon the most honorable of his creation, the faithful Prophet, and upon his pure familyThe pure ones and his companions, the noble ones, and after:PashtiThis is the second part of the book Explanation of the Problems of My Father's Poetry (Tamam)For my father Hamid Ahmed binAl-Kharzanji, who died in the year 348 AH.God Almighty has made it easy for me to publish the first part of it.). He wanted many brothersDistinguished researchers and professors to complete the collection and verification of the second part of it, and this desire has been fulfilled in the service of our heritageThe glorious Arab and the dissemination of crafts from him. I hope that this humble effort will be of benefit to the students of knowledge and scholarsand researchers.Praise be to God who guided us to this, and we would not have been guided had it not been for God to guide us, and my success is only through GodI entrusted him with repentance.Abu Tammam said he is proud of his people